Tourism Sustainability: Climate Change and Carbon Dioxide Emissions in South Africa - Jong, Meng-Chang; Soh, Ann-Ni; Puah, Chin-Hong (International Journal of Energy Economics and Policy, 2022)
In line with the 2030 Agenda of Sustainable Development initiated by the United Nations, a climate-resilient development strategy is in a need for the South African tourism. Following the principles of sustainable tourism development, the empirical analysis in this study intends to discover the dynamic relationship between climate change and tourism demand in South Africa. With the adoption of the “Triple Bottom Line” framework, our findings revealed the essential steps for South Africa to address the environmental, social, and economic factors necessary for the development of a sustainable tourism. By adopting the Autoregressive Distributed Lag (ARDL) approach, the present study confirmed that carbon emission leaves a negative impact on the tourism industry in South Africa. Therefore, it is crucial for the tourism practitioners and policy makers to improve the economic efficiency by paying more attention on the carbon dioxide emissions to balance the tourism development and environmental protection for long term sustainable growth for the South African tourism.